A Dream Deferred: The Microfoundations of Direct Political Action in Pre- and Post-democratisation South Africa. Issue 1 (2nd January 2016) - Bedasso, Biniam E.; Obikili, Nonso
Abstract : The stability of young democracies may be threatened by persistent protest as the economic legacies of the old autocratic regimes tend to outlive the defunct political structures. This paper seeks to explore the micro-level predictors of protest potential in South Africa before and after the end of apartheid. The results of the cohort analysis reveal that the political consciousness of the anti-apartheid struggle has a lasting effect. The gap between actual income and expected returns to education explains protest potential better than comparison of one's income with that of a reference group. The effect of race on protest potential has diminished over time.